2021
DOI: 10.3390/jof7080606
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin Biosynthesis, Genetic Regulation, Toxicity, and Control Strategies: A Review

Abstract: Aflatoxins (AFs) are highly toxic and cancer-causing compounds, predominantly synthesized by the Aspergillus species. AFs biosynthesis is a lengthy process that requires as minimum as 30 genes grouped inside 75 kilobytes (kB) of gene clusters, which are regulated by specific transcription factors, including aflR, aflS, and some general transcription factors. This paper summarizes the status of research on characterizing structural and regulatory genes associated with AF production and their roles in aflatoxige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 156 publications
0
27
0
1
Order By: Relevance
“…Generally, AFB1 is produced from a complicated biosynthetic pathway, including at least 28 enzymatic steps. The structural genes encoding these enzymes are grouped in one gene cluster while two cluster-specific regulators, aflR and aflS, mainly regulate their expression [34,35]. It was reported that the decrease in the transcription levels of aflatoxin genes was associated with a reduction in AFB1 production.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, AFB1 is produced from a complicated biosynthetic pathway, including at least 28 enzymatic steps. The structural genes encoding these enzymes are grouped in one gene cluster while two cluster-specific regulators, aflR and aflS, mainly regulate their expression [34,35]. It was reported that the decrease in the transcription levels of aflatoxin genes was associated with a reduction in AFB1 production.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that aflatoxin and ST biosynthesis in fungi are affected by the cluster‐specific transcription factors AflR and AflS, the sucrose non‐fermenting kinase SNF1, the heterotrimeric velvet complex VelB/VeA/LaeA, the global regulator NsdD, the sulfur metabolism transcription factor MetR, the heterotrimeric G‐protein FadA, the mitogen‐activated protein kinase‐related protein kinase ImeB, the Ras family GTPase RasA, and the histone deacetylase HdaA (Bayram et al ., 2008, 2009; Georgianna and Payne, 2009; Lee et al ., 2014; Li et al ., 2020; Yu et al ., 2020). Besides, the production of aflatoxin and ST is also tightly modulated by environmental stimulus and nutritional conditions, including temperature, pH, light, carbon source, nitrogen source and oxidative stress (Caceres et al ., 2020; Khan et al ., 2021). Previous study showed that white light has an obvious inhibition effect on ST formation in A. nidulans , compared to that in the dark (Bayram et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These harmful SMs are known generically as mycotoxins. One specially studied for its high toxicity is aflatoxin B1, produced by various species of Aspergillus [112]. Its consumption is associated with a syndrome known as acute aflatoxicosis, as well as with liver cancer or other damaging effects [103].…”
Section: Biological Properties and Applicationsmentioning
confidence: 99%